Discharge planning from hospital to home. - Shepperd, S; McClaran, J; Phillips, C; Lannin, N; Clemson, L; McCluskey, A; Cameron, I; Barras, S (2010)
BACKGROUND: Discharge planning is a routine feature of health systems in many countries. The aim of discharge planning is to reduce hospital length of stay and unplanned readmission to hospital, and improve the co-ordination of services following discharge from hospital. OBJECTIVES: To determine the effectiveness of planning the discharge of patients moving from hospital. SEARCH STRATEGY: We updated the review using the Cochrane EPOC Group Trials Register, MEDLINE, EMBASE and the Social Science Citation Index (last searched in March 2009). SELECTION CRITERIA: Randomised controlled trials (RCTs) that compared an individualised discharge plan with routine discharge care that was not tailored to the individual patient. Participants were hospital inpatients. DATA COLLECTION AND ANALYSIS: Two authors independently undertook data analysis and quality assessment using a predesigned data extraction sheet. Studies are grouped according to patient group (elderly medical patients, surgical patients and those with a mix of conditions) and by outcome. MAIN RESULTS: Twenty-one RCTs (7234 patients) are included; ten of these were identified in this update. Fourteen trials recruited patients with a medical condition (4509 patients), four recruited patients with a mix of medical and surgical conditions (2225 patients), one recruited patients from a psychiatric hospital (343 patients), one from both a psychiatric hospital and from a general hospital (97 patients), and the final trial recruited patients admitted to hospital following a fall (60 patients). Hospital length of stay and readmissions to hospital were significantly reduced for patients allocated to discharge planning (mean difference length of stay -0.91, 95% CI -1.55 to -0.27, 10 trials; readmission rates RR 0.85, 95% CI 0.74 to 0.97, 11 trials). For elderly patients with a medical condition (usually heart failure) there was insufficient evidence for a difference in mortality (RR 1.04, 95% CI 0.74 to 1.46, four trials) or being discharged from hospital to home (RR 1.03, 95% CI 0.93 to 1.14, two trials). This was also the case for trials recruiting patients recovering from surgery and a mix of medical and surgical conditions. In three trials patients allocated to discharge planning reported increased satisfaction. There was little evidence on overall healthcare costs. AUTHORS' CONCLUSIONS: The evidence suggests that a structured discharge plan tailored to the individual patient probably brings about small reductions in hospital length of stay and readmission rates for older people admitted to hospital with a medical condition. The impact of discharge planning on mortality, health outcomes and cost remains uncertain.